Enclosed Garden - Harangi, Attila; Török, Dávid; Kovács, Zsófia Mária (International Journal of Engineering and Management Sciences, 2017)
The archetype of the enclosed garden is the medieval hortus conclusus, which make the perfect type from the former types. The enclosed gardens of nowadays have developed from the hortus conclusus, which behave like a prism. Peter Zumthor’s Serpentine Gallery Pavilion is the best example for the contemporary hortus conclusus. The purpose of our study to make a typological collection about contemporary enclosed gardens. The base of the typology is the borderline of the garden, the wall of the garden. We based the study of borderline to Dom Hans van der Laan’s architectural theory and his monastery building in Vaals. We analyze the typology by six contemporary enclosed gardens from the simple wall to the building volume through the volumes of the wall. The openings of the walls can be the next way of our analysis.